2011
DOI: 10.1007/s10669-011-9321-1
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal mechanism of interactions between electromagnetic fields and biological systems: a calmodulin example

Abstract: The possible mechanisms of interactions of electromagnetic fields (EMF) with biological systems are often discussed in bioelectromagnetics in light of thermal versus nonthermal mechanisms. This paper attempts to show the principle difference between the biophysical and engineering approaches to biological mechanisms of EMF initiated bioeffects. While biophysical approach is based on experimentally obtained data on biological responses to the applied EMF, the engineering approach strongly relies on specific abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The other three models include: (3) electromagnetic induction in a) highly sensitive electric sensors (ampullae of Lorenzini) in Elasmobranchii fish [Kalmijn, ; Paulin, ] or in b) potentially specialized force receptors where negatively charged oligosaccharide side chains are covalently bound to ion channels in plasma membrane [Carrubba et al, ; Marino et al, ]; (4) the ion cyclotron resonance model that could affect ion transport rates and binding of ions to receptors under the influence of the GMF [Liboff, ; Liboff, ]; and (5) quantum coherence that has been found [Fleming et al, ; Lambert et al, ] or postulated in living organisms such as the coherent domains of water molecules proposed by Del Giudice et al []. It has also been shown that magnetic fields can change the intracellular level of Ca 2+ ions and can influence calmodulin‐dependent pathways that control several different biochemical pathways in plants [Funk et al, ; Pazur and Rassadina, ; Markov, ]. Some plant species may have additional structures that could be sensitive to a static magnetic field [Gajdardziska‐Josifovska et al, ; 2002].…”
Section: Discussionmentioning
confidence: 99%
“…The other three models include: (3) electromagnetic induction in a) highly sensitive electric sensors (ampullae of Lorenzini) in Elasmobranchii fish [Kalmijn, ; Paulin, ] or in b) potentially specialized force receptors where negatively charged oligosaccharide side chains are covalently bound to ion channels in plasma membrane [Carrubba et al, ; Marino et al, ]; (4) the ion cyclotron resonance model that could affect ion transport rates and binding of ions to receptors under the influence of the GMF [Liboff, ; Liboff, ]; and (5) quantum coherence that has been found [Fleming et al, ; Lambert et al, ] or postulated in living organisms such as the coherent domains of water molecules proposed by Del Giudice et al []. It has also been shown that magnetic fields can change the intracellular level of Ca 2+ ions and can influence calmodulin‐dependent pathways that control several different biochemical pathways in plants [Funk et al, ; Pazur and Rassadina, ; Markov, ]. Some plant species may have additional structures that could be sensitive to a static magnetic field [Gajdardziska‐Josifovska et al, ; 2002].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction mechanisms may be very complex as is the living tissue itself, thus state of the art physics, chemistry and biology will be required to identify them. Indeed, initial interesting research attempting this has been reported, see for example [8] with its many references and [9].…”
Section: Introductionmentioning
confidence: 99%